Risk management in early banking : an international perspective of swedish savings banks, 1820-1910 /: an international perspective of swedish savings banks, 1820-1910. (2021) - Larsson, Mats, 1953-; Lilja, Kristina, 1968-; Petersson, Tom
No abstract available